GURU PROFESIONAL DALAM PERSPEKTIF AL QURAN DAN HADIS - Syah, Zaimir; AM, Rusydi; Charles, Charles (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
Education as a theory in the form of human thinking about educational problems and efforts to solve them fundamentally and systematically. Professionalism is an understanding that prohibits that every job must be done by a professional. Profession is a person who runs a profession. In Islam all work must be done professionally in the sense that it must be done correctly. This research method is a qualitative research with a literature study approach. The data used in this study are in the form of document data, both from the Koran, al-Hadith, textbooks, scientific journals, and other relevant document sources. In terms of this literature study approach, the researcher looked for literature or library data in the form of teacher professionalism according to the perspective of the Koran and al hadith. The results of the study show that professional work must be matched with expertise. Teacher professionalism in the Koran shows that teachers must have democratic characteristics, be patient and gentle in carrying out their noble duties, forgive and be consistent with their duties and responsibilities, be able to work together (cooperative) and be compassionate both in action and in the form of prayer.